Iskolai szegregáció, szabad iskolaválasztás és helyi oktatáspolitika 100 magyar városban - Gábor Kertesi; Gábor Kézdi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
– The distribution of Roma and non-Roma students across schools has become considerably more unequal in Hungary since the 1980's. This paper analyzes the effect of school choice and local educational policies on that inequality, known as school segregation, in 100 Hungarian towns. We combine administrative data with data from a survey that we collected from municipality administrations with respect to local educational policies and the ethnic composition of neighborhoods. Our results indicate that in Hungarian towns, free school choice diminishes the role of residential distribution because many students commute to schools of their choice. Towns where such commuting is more pronounced are characterized by stronger inter-school inequalities. We also find that local educational policies have, on average, somewhat segregationist tendencies, though there is substantial heterogeneity across towns. The more segregationist the local policies are, the higher the segregation in the town, thus suggesting that local policies have room to influence school segregation in this system. However, the impact of local educational policies is weaker than the role of school choice.
Keywords: I24; I28; J15; 330; School segregation; Roma minority; school choice; local educational policies